Final Year Project Progress Monitoring System - Mohd Hisham, Nor Maisarah (IRC, 2020)
As part of the requirements to graduate, all final year students are required to take the Final Year Project (FYP) course offered by Universiti Teknologi Petronas (UTP). This course is divided into two phases, which are FYP1 and FYP2 that run for two semesters. One of the problems faced during the project's development is the absence of a systematic approach to monitor the students’ FYP progress. Supervisors were therefore confronted with challenges in handling students and their tasks. Currently, there is no FYP monitoring system that is being implemented in UTP. Project monitoring system is a tool that enables the monitoring and management of projects within the scope of works and expenditures. It is a tool created for everyone that is responsible for the management of the entire project portfolio. The aim of this project is to recommend incorporating the Final Year Project Progress Monitoring System to track and monitor the development of the student's project. The mobilebased system will be designed to improve interaction between students and supervisors, increasing supervisory productivity and thus enhancing students’ chances of improving their project outcome.